Principal Leadership Strategy In Improving Teacher Performance And Learning Quality In Junior High Schools - Bambang Ismaya (SABA JAYA PUBLISHER, 2024)
This study aims to analyze the principal's leadership strategy in improving teacher performance and learning quality in Junior High Schools (SMP). The study was conducted qualitatively with descriptive-analytic methods at SMP Negeri 3 Ambara, Semarang Regency. Data collection was carried out through interviews, observations, and documentation. The results showed that principals who implemented transformational leadership succeeded in increasing teacher motivation and commitment. Effective strategies include routine supervision, teacher training, creating a conducive school climate, and consistent learning evaluation. Routine supervision provides constructive feedback to teachers, while a conducive school climate encourages collaboration and innovation in the learning process. However, several obstacles were found, such as time constraints and the difficulty of building collaboration between teachers in an individualistic environment. Overall, this study confirms that effective principal leadership plays an important role in improving teacher performance and the quality of education in schools.